The woman who outshone the sun = La mujer que brillaba aun mas que el sol - Zubizarreta-Ada, Rosalma (San Francisco : Childrens Book, 1991)
Text in English and Spanish. Retells the Zapotec legend. . .
5.1
3-6
3-6
Elem. School Library Collection
School Library Journal
Book Links (A.L.A.)
Keywords: Spanish language materials -- Bilingual; Zenteno, Lucia (Legendary character); Zapotec Indians -- Legends; Indians of Mexico -- Legends; Zenteno, Lucia (Legendary character); Zapotec Indians -- Legends; Bilingual books -- English-Spanish.; Native Americans -- Mexico -- Legends